Transformative Educational Leadership In Bridging Cultural Studies, Organizational Management And Innovation For Adaptive Learning Environments - Nur Efendi (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates how transformative educational leadership bridges cultural studies, organizational management, and innovation to develop adaptive learning environments at MAN 1 Trenggalek. The research addresses three main issues: the integration of cultural values in organizational management, the role of leadership in fostering innovation, and the interaction among these elements in shaping adaptability. A qualitative case study design was employed, involving the principal, teachers, and administrative staff selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis, then analyzed using thematic procedures including coding, categorization, and interpretation. The findings reveal that transformative leadership aligns cultural awareness with participatory management and innovation-oriented practices. Cultural values influence decision-making, communication, and professional relationships, strengthening institutional cohesion. Management practices support adaptive learning through collaborative planning, reflective evaluation, and flexible instruction. Innovation emerges through interdisciplinary and context-based teaching approaches responsive to student needs. The study concludes that the dynamic alignment between leadership, culture, management, and innovation is essential in creating responsive, sustainable, and adaptive educational environments.